Exploring the Determinants of Digital Banking Adoption Among Islamic Banks in Indonesia - Nanang Setiawan; Alfa Rahmiati (International Conference on Islamic Economic (ICIE), 2025)
: This study analyzes the critical factors influencing the adoption of digital banking services within Islamic banks in Indonesia. The rapid digital transformation in the Islamic financial sector has created both opportunities and challenges, particularly in understanding customer behavior and aligning digital innovations with Sharia principles. The primary objective of this research is to identify the extent to which religiosity, financial literacy, business expectations, and social influence affect the willingness of Muslim users to adopt digital banking platforms. A quantitative survey method was applied, involving 265 Muslim students from various universities in East Java, Indonesia, who actively utilize digital banking services. The results demonstrate that religiosity is the most significant determinant of adoption, highlighting that faith-based values strongly shape consumer decisions in the Islamic financial context. In addition, financial literacy, perceived business benefits, and peer influence were also found to have a substantial impact, reflecting the role of both intrinsic and extrinsic motivators. These findings contribute to the growing body of knowledge on technology acceptance in Islamic finance by integrating behavioral and spiritual perspectives. The study also offers practical insights for Islamic banks to design digital services that are both technologically innovative and ethically aligned with customers’ expectations